Strain glass by aging in Ti–Pd–Fe shape memory alloys. (1st March 2020) - Ren, Shuai; Liu, Chang; Chen, Xuan; Hao, Yanshuang; Ren, Xiaobing
Abstract: Up to now, most of strain glasses are achieved by doping point defects into martensitic alloys. Here we report a strain glass in a Ti54 Pd36 Fe10 shape memory alloy achieved by low-temperature aging. Aging at 523 K generates Ti2 Pd-like nanoprecipitates, which are responsible for the formation of strain glass. By continuously increasing the aging time, we studied how the strain glass transition gradually evolves from a martensitic transformation. A short aging time (12 min) is enough to generate strain glass, while the martensite still persists as the aging time increases to 300 min. A temperature–aging time phase diagram is established accordingly. Grahpical abstracts: Image, graphical abstract